Condition and body constitution of soccer players in category U19 before and after completing a preparatory period - Botek, Z.; Gaba, A.; Lehnert, M.; Pridalova, M.; Varekova, R.; Botek, M.; Langer, F. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2010)
BACKGROUND: The level of one's conditioning predisposition and somatic factors are one of the main components determining the quality of an individual's performance in soccer. OBJECTIVE: The aim of this study was to evaluate changes in selected motor, functional and somatic parameters of soccer players in category U19, who completed the long used model of a training program employed in the preparatory period of soccer players. METHODS: The monitored group was composed of 14 players from SK Sigma Olomouc in category U19. The categories being evaluated comprised: their starting and acceleration speeds in the 10 m, 30 m and 30 m sprint with a flying start, the vertical jump, the isokinetic muscular strength of the knee joint and their maximum aerobic capacity. Of the monitored somatic factors attention was mainly focused on body height and weight, percentage of body fat, quantity of fat free mass and the overall amount of water in their bodies. RESULTS: From the spectrum of examined motor and functional parameters the only value that changed significantly with the players was the average value of VO2max from 56.65 to 58.85 ml.kg-1.min-1 (p = 0.04). Among the somatic factors a significant decrease was seen with the values of the Body Mass Index from 22.51 to 22.28 kg.m-2 (p = 0.03). CONCLUSIONS: In the context of the players' performance the expected changes of the monitored parameters were not observed. It is believed that the traditional model of soccer players' preparation does not lead to the desired changes in conditioning and somatic parameters.